DOLPHIN ASSISTED THERAPY: WELFARE OF BOTH PATIENTS WITH DEPRESSION AND PARTICIPATING DOLPHINS - Kreiviniene, Brigita; Lupeikaitė, Laura; Bredelytė, Aelita; Kleiva, Žilvinas (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The main aim of this research was to measure the effect of dolphin assisted therapy on both patients and participating dolphins. The research measured welfare of patients with depression and situational welfare of dolphins which participated in the dolphin assisted therapy programme. Patients with organic depression took part in two-week dolphin assisted therapy sessions. When measuring situational welfare of dolphins, the study sample consisted of nine individual dolphins (Tursiops truncatus ponticus, Lat.): three males and six females ranging from five to twenty years. The main research results revealed that psychosocial characteristics of patients with organic depression disorder as well as patients’ self-evaluation changed statistically significantly, the symptoms of depression decreased. The research revealed that patients were much more physically active during the period of participation in the dolphin assisted therapy process than before. The analysis of dolphin behaviour brought to the light that most of the therapy time dolphins behaved positively. There were noticed no therapy sessions where the dolphin behaviour would be evaluated as more negative than positive or just negative.